Association of mitochondrial haplogroups and cognitive impairment in the Amish. (20th December 2022) - Dorfsman, Daniel A.; Prough, Michael B.; Caywood, Laura J.; Clouse, Jason E.; Herington, Sharlene D.; Slifer, Susan H.; Adams, Larry D.; Laux, Renee A.; Song, Yeunjoo E.; Lynn, Audrey; Fuzzell, M. Denise; Fuzzell, Sarada L.; et al.
Abstract: Background: Mitochondrial dysfunction is an important feature of Alzheimer's Disease (AD) pathogenesis. Reduced glucose utilization and increased oxidative stress are intermediates through which impaired mitochondria may promote AD‐associated brain changes. Association between groups of variants ("haplogroups") in the mitochondrial genome and AD have been reported for haplogroups U, J, and K. To test these effects in the Amish, we looked for evidence of association between AD‐associated haplogroups and cognitive impairment in a sample of aged Amish individuals. Method: Cognitive status in adult Amish participants (n=670) with whole‐genome sequence (WGS) data was determined based on modified mini‐mental status exam results (3MS). An outcome of cognitively impaired (CI) was assigned to individuals with an education‐adjusted 3MS < 87 at any age. A status of cognitively unimpaired (CU) was assigned to those aged ≥ 75 scoring ≥ 87 on the 3MS. Mitochondrial variants detected by WGS were used to derive broad haplogroups for each sample using Haplogrep2. Mixed model association testing was performed in GENESIS with CI as the outcome, and haplogroup (U, J, or K), APOE ε4 carrier status (ε4 vs no ε4), sex, and age as predictors. Based on reports of sex‐specific haplogroup U effects on AD, a sex‐stratified analysis was conducted. A random‐effect kinship matrix was used to account for relationships. Result: Association between mitochondrial haplogroups U, J, or K and CI was not observed at a 5% significance level. The sex‐stratified analysis showed the strongest association of CI with haplogroup U (OR 1.8, 95% CI 0.92‐3.5) among women. Among men, the estimated effect was 0.77 (95% CI 0.37‐1.62). The overall direction of association was opposite in men and women, though neither was statistically significant at 5%. Conclusion: Although significant evidence of a haplogroup effect on cognitive status was not observed, the moderate sex‐dependent effect of haplogroup U on impairment warrants further examination in an expanded dataset.Previously, haplogroup U was proposed as an AD risk factor among men, whereas it appears as a risk factor for CI in women in the present study.